2016
DOI: 10.2196/mental.4822
|View full text |Cite
|
Sign up to set email alerts
|

Validating Machine Learning Algorithms for Twitter Data Against Established Measures of Suicidality

Abstract: BackgroundOne of the leading causes of death in the United States (US) is suicide and new methods of assessment are needed to track its risk in real time.ObjectiveOur objective is to validate the use of machine learning algorithms for Twitter data against empirically validated measures of suicidality in the US population.MethodsUsing a machine learning algorithm, the Twitter feeds of 135 Mechanical Turk (MTurk) participants were compared with validated, self-report measures of suicide risk.ResultsOur findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(108 citation statements)
references
References 53 publications
0
105
0
3
Order By: Relevance
“…The instruments used to detect suicidal ideation and the possibility of an individual committing suicide were the Suicide Probability Scale [32,39,48], the Acquired Capability for Suicide Scale [30], and the Interpersonal Needs Questionnaire [30]. Satisfaction with life and well-being were measured with the Satisfaction with Life Scale [28,34], the Positive and Negative Affect Schedule [55], and the Psychological Well-Being Scale [55].…”
Section: Resultsmentioning
confidence: 99%
“…The instruments used to detect suicidal ideation and the possibility of an individual committing suicide were the Suicide Probability Scale [32,39,48], the Acquired Capability for Suicide Scale [30], and the Interpersonal Needs Questionnaire [30]. Satisfaction with life and well-being were measured with the Satisfaction with Life Scale [28,34], the Positive and Negative Affect Schedule [55], and the Psychological Well-Being Scale [55].…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning approaches have been used to predict health related issues and behaviors through social media [25,47], electronic health records [48,49], and accelerometer data [50]. As illustrated through the application of a pruned decision tree analysis (see Figure 2) of Twitter data, the model capably predicts ED with 91% accuracy among identified followers of …”
Section: Discussionmentioning
confidence: 99%
“…In the same line of research, O'Dea et al [18] confirmed that Twitter is used by individuals to express suicidality and demonstrated that it is possible to distinguish the level of concern among suiciderelated tweets, using both human coders and an automatic machine classifier. These insights have also been investigated by Braithwaite et al [19] who demonstrated that machine learning algorithms are efficient in differentiating people who are at a suicidal risk from those who are not. For a more detailed review of the use of social media platforms as a tool for suicide prevention, the reader may refer to the recent systematic survey by Robinson et al [20].…”
Section: Literature Reviewmentioning
confidence: 93%